Single Use Laminate BIOMEMS as Rich Featured Labs-on-Chip. (2015) - Jobst, Gerhard
Abstract: Low volume multi-parameter LoCs for the monitoring of metabolic parameters and flow rate with integrated micro-pumps intended for single-use applications are enabled by cost-effective polymer laminate-based manufacture with wafer-level μFluidics packaging. Integration of flow rate sensing and pumping to these biosensors based BIOMEMS is enabling for the reliable biotechnology and medical application.